Evaluación del porcentaje de níquel recuperado proveniente de catalizador agotado del cracking de petróleo mediante lixiviación asistida por ultrasonido - Zevallos Torres, Luis Alberto (2016)
The aim of this project was to evaluate the recovery percentage of Ni from a spent catalyst used in hydrocarbon cracking in Talara Refinery in Piura using ultrasound lixiviation with 3 different organic acids such as tartaric, citric and oxalic acid. The acids concentrations used were 1,0 and 2,0 mol/L, the temperatures were set at 25 and 70’C, and a constant lixiviation time of 3 hours was used for all the experiments. The statistical analysis about the influence of the independent variables (acid concentration, temperature and use of ultrasound) on the recovery percentage of Ni shows that both temperature and use of ultrasound are the factors that have more influence on the dependant variable; where the temperature is he factor that has much more influence of both. On the other hand, the quantitative analysis results of the recovery percentage of Ni, using different acids, show that oxalic acid 1,0 M at 70’C and with ultrasound application at 40 KHz for 3 hours had the biggest recovery percentage of 24,92% approximately. This study allows us to conclude that organic acids have a potential to lixiviate metals in an environmentally friendly way.